Analysis of the effect of fabric parameters on sound related properties of blended fabrics - Niroshan, T.S.; Madushika, J.W.A.; Niles, S.N. (University of Jaffna, 2021)
Sound is a form of energy which is carried by sound waves. Sound may be reflected, transmitted, absorbed or diffused. Various applications may require the absorption or reduced transmission or reflection of sound. Textile fabrics have been used extensively for this purpose. Non-woven fabrics with different properties play a significant role in sound related properties because of their high porosity, low cost, low weight and low environmental impact. Despite this fact, woven and knitted fabrics are preferred in some sound related end-uses where nonwoven and spacer textiles cannot be used economically and due to aesthetic aspects. The aim of this research is to analyse how sound related properties of Polyester/Cotton blended fabrics would vary with different fabric parameters, namely thickness, composition and areal density. For this study a low cost impedance tube was built and experiments were carried out using the equipment developed. The frequency of the emitted sound was varied and their pressure levels monitored and converted to required parameters. The effect of thickness,composition and areal density on sound related properties of woven fabrics was investigated. The test results showed that, in case of increasing the thickness, the sound absorption and reflection coefficients of fabrics increased at low frequencies and slightly decreased at high frequencies. The transmission characteristics were opposite to that. 100% polyester had the highest sound absorption and the 100% cotton fabric had the second highest sound absorption. Moreover, test results revealed that denser fabrics absorb more sound waves than reflection or transmission in high frequencies.
Keywords: Sound reflectance; Sound transmission; Sound absorption; Sound diffusion; spacer textiles; Areal density; Impedance tube; Acoustic textiles